The Themes of ’Proactivity’ and ’Reactivity’ in Achebe’s ’Marriage is a Private Affair’ - Hussein, Khalid Mahmoud (European Scientific Journal, ESJ, 2022)
The present study sets out to investigate the themes of ’proactivity’ and ’reactivity’ in Chinua Achebe’s ’Marriage is a Private Affair’. First, definitions for these concepts are established, and then the main characters’ responses which run in their speeches and actions are pored over considering these definitions. Throughout the present study, ’proactivity’ and ’reactivity’ are construed as conscious cognitive choices rather than personality traits and acting proactively or reactively (assertively or submissively) is beheld as contextually bound and as determined by what floats on the surface rather than by what hides in the unconscious. Drawing upon the critiques of the concepts of ’proactivity’ and ’reactivity’, and having in mind that ’proactivity’ and ’reactivity’, as their lexical meanings may suggest, are two ends for the same dimension of doing something, one could safely claim that despite all Nene’s(a character) proactive efforts to cultivate friendship with her in-laws, only after going some way towards the traditional position and reacting positively to the socially- imposed patterns considered to be crucial determinants of her acceptance in the extended family network she is admitted in the cosmopolitan Ibo community. Finding her feet there, she partakes in the construction of a new more open and accommodating Ibo identity. Two other important themes that seem to emerge strongly in the present study are that marriage is a tribal matter that should be framed within allegiance and respect for family traditions and religious affiliation, and that family can tackle any problem if its members stand as one strong front against any external antagonistic power.